The goose that laid golden eggs - Robbins; Rita (Jamaica Mind to Mind, 2016)
The fable teaches a valuable lesson about the dangers of greed and the importance of appreciating what you have. Through simple language and engaging illustrations, the book conveys that being satisfied with what you have is often better than seeking more and losing everything.